More Than Mileage: The Preconditions of Travel and the Real Burdens of H.B. 2 - Gomez, Madeline M. (Columbia Journal of Gender and Law, 2016)
During the winter break of my second year in law school, I drove from my childhood home in Fort Worth, Texas to New Orleans, Louisiana to watch oral arguments at the Fifth Circuit in the case Planned Parenthood v. Abbott. 1 That case was the first legal challenge to the constitutionality of Texas House Bill 2 (“H.B. 2”),2 the omnibus anti-abortion bill enacted by the Texas legislature in 2013. In total, I drove 541 miles door-to-door, spending about eight hours on the road each way. That distance is slightly less than what a woman living in El Paso would have to travel to get an abortion in Texas if H.B. 2 had been fully implemented. Because of the Supreme Court’s decision in Whole Woman’s Health v. Hellerstedt,3 the second attempt to strike down the law, that potential outcome will hopefully remain a hypothetical.